PENGARUH PEMBERIAN PUPUK BOKASHI DAN ZEOLIT SEBAGAI BAHAN PEMBENAH TANAH TERHADAP KETERSEDIAAN NITROGEN TANAH REGOSOL - Anna Febya Narulita; R. Agus Widodo; Miseri Roeslan Afany (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Regosol has been widely used for agricultural production despite its low nutrient availability and adsorption. This research aimed to know the effects of bokashi and zeolite on the availability of nitrogen (N) in Regosol. The experiment was carried out with a completely randomized 2-factors design. The first factor was bokashi, with three levels: 0 t ha-1 (B0), 20 t ha-1 (B1), and 30 t ha-1 (B2). The second factor was zeolite with three levels: 0 t ha-1 (Z0), 5 t ha-1 (Z1), and 10 t ha-1 (Z2). Each treatment was repeated three times. Each treatment was incubated for 30 days. The parameters before being treated were texture, bulk density, pH H2O, N-totals, C-organic, available N, and CEC in soil, pH H2O, N-totals, available N, and C-organic in bokashi, also CEC in the zeolite. The parameters after being treated were pH H2O, N-totals, C-organic, C/N, available N, and CEC in soil, also leached NH4+ and leached NO3- in water. The data were analyzed with ANOVA followed by the DMRT at a 5% level. The results showed that bokashi significantly affected the available N, pH H2O, N-total, leached NO3-, and CEC, meanwhile zeolite did not significantly affect the available N but significantly affected the N-totals, C/N in soil, and leached NO3-. The combination of bokashi and zeolite did not significantly affect the available N in the soil. The best dose of bokashi increasing available N of Regosol was at a dose of 20 t ha-1 (B1).